Three-Dimensional Cd(II) Coordination Compound with a-Po Topology Framework - Sheng, Jianmin (Asian Journal of Chemistry, 2010)
The pyridinecarboxylato-bridged coordination polymer of cadmium(II) with the formula [Cd(pbc)2] (Hpbc = 3-pyrid-3-ylbenzoic acid) has been synthesized by the hydrothermal method and characterized by X-ray single crystal diffraction. In compound [Cd(pbc)2], the ligands act as bridging ligands exhibiting rich coordination modes to link metal ions. The pbc– groups bridge Cd(II) ions to an infinite 3D framework.